Targeting Tumor-Associated Macrophages and Inhibition of MCP-1 Reduce Angiogenesis and Tumor Growth in a Human Melanoma Xenograft - Gazzaniga, Silvina Noemí (2007)
Chemokines such as monocyte chemoattractant protein (MCP)-1 are key agonists that attract macrophages to tumors. In melanoma, it has been previously shown that variable levels of MCP-1/CCL2 appear to correlate with infiltrating macrophages and tumor fate, with low to intermediate levels of the chemokine contributing to melanoma development. To work under such conditions, a poorly tumorigenic human melanoma cell line was transfected with an expression vector encoding MCP-1. We found that M2 macrophages are associated to MCP-1+ tumors, triggering a profuse vascular network. To target the protumoral macrophages recruitment and reverting tumor growth promotion, clodronate-laden liposomes (Clod-Lip) or bindarit were administered to melanoma-bearing mice. Macrophage depletion after Clod-Lip treatment induced development of smaller tumors than in untreated mice. Immunohistochemical analysis with an anti-CD31 antibody revealed scarce vascular structures mainly characterized by narrow vascular lights. Pharmacological inhibition of MCP-1 with bindarit also reduced tumor growth and macrophage recruitment, rendering necrotic tumor masses. We suggest that bindarit or Clod-Lip abrogates protumoral-associated macrophages in human melanoma xenografts and could be considered as complementary approaches to antiangiogenic therapy.